Too clever to see - Taylor, Kim. (London : Belitha press, 1990)
Text and photographs introduce animals who, by a variety of means, make it difficult for the human (and other animal) eyes to see.
Includes index.
Keywords: Camouflage (Biology) -- Juvenile literature; Mimicry (Biology) -- Juvenile literature; Visual discrimination -- Juvenile literature